2015
DOI: 10.1007/s00595-015-1186-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of hyaluronic acid/sodium alginate-based microparticles to prevent tissue adhesion in a rabbit model

Abstract: MP shows potential as an effective novel type of resorbable biomaterial to reduce postoperative adhesion. The easy placement and handling of this material make the MP powder attractive as a tissue adhesion barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…This high-density polymer shows high viscosity, viscoelasticity, and water-retaining capacity, and could therefore function as a lubricant 18. Additionally, hyaluronic acid is biocompatible, biodegradable (completely degrades within 5 days), and nontoxic, which enhances its popularity as a barrier agent 18,21. In earlier studies, hyaluronic acid was not found to reduce adhesion formation or reformation 28,29.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This high-density polymer shows high viscosity, viscoelasticity, and water-retaining capacity, and could therefore function as a lubricant 18. Additionally, hyaluronic acid is biocompatible, biodegradable (completely degrades within 5 days), and nontoxic, which enhances its popularity as a barrier agent 18,21. In earlier studies, hyaluronic acid was not found to reduce adhesion formation or reformation 28,29.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, numerous studies are now focused on nonpharmacological agents to prevent adhesions. Nonpharmacological anti-adhesive agents are available in many forms, including liquid, membrane, and textile embodiments, and they mainly provide a physical barrier between adjacent peritoneal surfaces and organs, thus reducing adhesion formation/reformation in clinical use 21. ORC and hyaluronic acid are frequently used anti-adhesive agents in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…It can be inferred that the application of the hyaluronic acid gel is better than an IUD or balloon at improving the pregnancy rate after IUA separation. It was also demonstrated that hyaluronic acid can regulate inflammatory factors, promote the normal epithelialization and regeneration of wound tissues, effectively isolate adjacent healing tissues and prevent the formation of adhesions (30).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 In addition to wound healing, investigators have also evaluated alginate’s effect on fibrosis. Back et al 15 showed that alginate-impregnated dressing caused significantly less postoperative adhesion and fibrosis after experimental laparotomy in the rabbit model. Alginate-coated silicone sheeting has been used to deliver dexamethasone to the middle ear mucosa of guinea pigs, which showed favorable decreases in fibrosis.…”
Section: Discussionmentioning
confidence: 99%